The KdpFABC complex – K+ transport against all odds. (1st January 2019) - Pedersen, Bjørn P.; Stokes, David L.; Apell, Hans-Jürgen
Abstract: In bacteria, K + is used to maintain cell volume and osmotic potential. Homeostasis normally involves a network of constitutively expressed transport systems, but in K + deficient environments, the KdpFABC complex uses ATP to pump K + into the cell. This complex appears to be a hybrid of two types of transporters, with KdpA descending from the superfamily of K + transporters and KdpB belonging to the superfamily of P-type ATPases. Studies of enzymatic activity documented a catalytic cycle with hallmarks of classical P-type ATPases and studies of ion transport indicated that K + import into the cytosol occurred in the second half of this cycle in conjunction with hydrolysis of an aspartyl phosphate intermediate. Atomic structures of the KdpFABC complex from X-ray crystallography and cryo-EM have recently revealed conformations before and after formation of this aspartyl phosphate that appear to contradict the functional studies. Specifically, structural comparisons with the archetypal P-type ATPase, SERCA, suggest that K + transport occurs in the first half of the cycle, accompanying formation of the aspartyl phosphate. Further controversy has arisen regarding the path by which K + crosses the membrane. The X-ray structure supports the conventional view that KdpA provides the conduit, whereas cryo-EM structures suggest that K + moves from KdpA through a long, intramembrane tunnel to reach canonical ion binding sites in KdpB from which they are released to the cytosol. This review discusses evidence supporting these contradictory models and identifies key experiments needed to resolve discrepancies and produce a unified model for this fascinating mechanistic hybrid.